ANALYSIS OF LOAD-BEARING MESHING CHARACTERISTICS OF CYCLOIDAL PINWHEEL OF RV REDUCER BASED ON FINITE ELEMENT MODELING (MT) - LIANG Qiang; CHENG Cheng; SHI BaoJun (Jixie qiangdu)
In order to study the influence of load change on the meshing characteristics of cycloid pinwheel of RV reducer, considering the modification of cycloid tooth profile, the three-dimensional model of cycloid pinwheel mechanism was established by UG. The changes of meshing tooth pairs and meshing stress of cycloid pinwheel in a meshing transmission cycle were analyzed by using the transient dynamics module of Ansys, and the simulation was compared with the theoretical contact stress. Results show that the overall trend of contact stress between simulation and theory is consistent, the number of meshing teeth and meshing stress of cycloid pinwheel show a periodic law, and increase with the increase of load. The change trend of contact stress and equivalent stress is opposite to the number of meshing teeth, the more the number of meshing teeth, the smaller the meshing stress. The equivalent stress of the needle tooth in the length direction increases with the increase of load, and the stress has a trend of uniform distribution, but the change is small. The finite element analysis has certain reference significance for the design, analysis and manufacture of RV reducer.